2021
DOI: 10.15252/embj.2020104913
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial transcription factor activities on open chromatin induce embryonic heterogeneity in vertebrates

Abstract: During vertebrate gastrulation, mesoderm is induced in pluripotent cells, concomitant with dorsal-ventral patterning and establishing of the dorsal axis. We applied single-cell chromatin accessibility and transcriptome analyses to explore the emergence of cellular heterogeneity during gastrulation in Xenopus tropicalis. Transcriptionally inactive lineage-restricted genes exhibit relatively open chromatin in animal caps, whereas chromatin accessibility in dorsal marginal zone cells more closely reflects transcr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…The rapid development of high-throughput single-cell RNA sequencing (scRNA-seq) technology offer a good opportunity to dissect cell heterogeneity of Xenopus , from embryogenesis 1 , 2 to individual organs such as cornea and kidney 3 , 4 , and to reveal the cellular mechanism of Xenopus regeneration such as in limb 5 , 6 , tail 7 , 8 and spinal cord 9 . A large number of organism-wide single-cell atlases have been constructed for various species, such as Homo sapiens 10 , Macaca fascicularis 11 , Mus musculus 12 , Danio rerio 13 , Drosophila melanogaster 14 , Ciona intestinalis 15 , Caenorhabditis elegans 16 , Schmidtea mediterranea 17 , and Stylophora pistillata 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of high-throughput single-cell RNA sequencing (scRNA-seq) technology offer a good opportunity to dissect cell heterogeneity of Xenopus , from embryogenesis 1 , 2 to individual organs such as cornea and kidney 3 , 4 , and to reveal the cellular mechanism of Xenopus regeneration such as in limb 5 , 6 , tail 7 , 8 and spinal cord 9 . A large number of organism-wide single-cell atlases have been constructed for various species, such as Homo sapiens 10 , Macaca fascicularis 11 , Mus musculus 12 , Danio rerio 13 , Drosophila melanogaster 14 , Ciona intestinalis 15 , Caenorhabditis elegans 16 , Schmidtea mediterranea 17 , and Stylophora pistillata 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The genomic resources generated here will thus provide important tools for further studies. Given the crucial role of X. tropicalis for genomic analysis of development and regeneration 114,115 , the improvements to our understanding of its genome reported here will provide a more finely grained view of biomedically important genetic and epigenetic mechanisms. This new genome is also important from the standpoint of evolutionary genomics, as comparisons between the genomes of X. tropicalis and X. laevis shed light on mechanisms of genome duplication 115 .…”
Section: Discussionmentioning
confidence: 99%
“…During the blastula stage of embryonic development, zygotic gene activation occurs, which is called the mid-blastula transition (MBT) 53 , 54 . It has been reported that the open chromatin accessibility for gene expression becomes higher after MBT (at least after stage 9) in Xenopus ACs 55 . Our transcriptome data using ACs dissected from blastula demonstrated the dynamic expression of various epigenetic regulators, which increase chromatin accessibility and lead to acceleration of gene transcription.…”
Section: Discussionmentioning
confidence: 99%